Non-cell autonomous and spatiotemporal signaling from a tissue organizer orchestrates root vascular development - Yang, BaoJun (Nat Plants, 2021)
During plant development, a precise balance of cytokinin is crucial for correct growth and patterning, but it remains unclear how this is achieved across different cell types and in the context of a growing organ. Here we show that, in the root apical meristem, the TMO5/LHW complex increases active cytokinin levels via two cooperatively acting enzymes. By profiling the transcriptomic changes of increased cytokinin at single cell level, we further show that this effect is counteracted by a tissue specific increase in CYTOKININ OXIDASE 3 expression via direct activation of the mobile transcription factor SHORTROOT. In summary we show that within the root meristem, xylem cells act as a local organizer of vascular development by non-autonomously regulating cytokinin levels in neighboring procambium cells via sequential induction and repression modules.